2003
DOI: 10.1063/1.1572132
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of bound and resonance states of HO2 for nonzero total angular momentum

Abstract: Bound and resonance states of HO 2 have been calculated quantum mechanically by the Lanczos homogeneous filter diagonalization method ͓Zhang and Smith, Phys. Chem. Chem. Phys. 3, 2282 ͑2001͒; J. Chem. Phys. 115, 5751 ͑2001͔͒ for nonzero total angular momentum Jϭ1,2,3. For lower bound states, agreement between the results in this paper and previous work is quite satisfactory; while for high lying bound states and resonances these are the first reported results. A helicity quantum number ⍀ assignment ͑within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…5 The potential energy surface (PES) of HO 2 (X 2 A ) has been much studied at various levels of ab initio theory. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] It is key both for calculations of bound vibrational states and resonances [22][23][24][25][26][27][28][29] as well as reactive scattering either via time-independent or time-dependent methods. 22,[30][31][32][33][34][35][36][37][38][39] Three PESs have been mostly utilized: Melius-Blint, 6 double manybody expansion (DMBE IV 16 ), and diatomics-in-molecules (DIM) 17 (as slightly updated; 40 a related form is available 41 but not yet used for dynamics).…”
Section: Introductionmentioning
confidence: 99%
“…5 The potential energy surface (PES) of HO 2 (X 2 A ) has been much studied at various levels of ab initio theory. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] It is key both for calculations of bound vibrational states and resonances [22][23][24][25][26][27][28][29] as well as reactive scattering either via time-independent or time-dependent methods. 22,[30][31][32][33][34][35][36][37][38][39] Three PESs have been mostly utilized: Melius-Blint, 6 double manybody expansion (DMBE IV 16 ), and diatomics-in-molecules (DIM) 17 (as slightly updated; 40 a related form is available 41 but not yet used for dynamics).…”
Section: Introductionmentioning
confidence: 99%
“…TIQM calculations on H+O 2 reaction are extended to total angular momentum J>0 and Coriolis coupling was explicitly included [27,[62][63][64], which revealed that the importance of Coriolis coupling increases with J increasing. Due to its extensive Coriolis coupling, HO 2 system served as a rigorous benchmark for helicity conserving method and Jshifting models [65][66][67][68]. Poirier et al [69][70][71] addressed approximated quantum dynamics calculations on the HO 2 bound rovibrational state using various theorybased J-shifting schemes.…”
Section: The Ho2 Systemmentioning
confidence: 99%
“…However the approximation can fail for certain molecular systems. HO 2 , for example, is one of those cases in which the comparison [37][38][39] between some of these decoupling schemes and calculations performed with methods such as the ScallT program developed by Poirier and collaborators [40,41] or the Chebyshev filter diagonalization method employed by Zhang and Smith [42][43][44][45] reveals the necessity of a proper account for the Coriolis coupling terms.…”
Section: Contentsmentioning
confidence: 99%
“…Ω, and the index v Γ of the corresponding vibrational state in each irreducible representation (see Eqs. (41)(42)(43)) are given in the first, third and fourth columns, respectively. The rovibrational Γ Ω vib (fifth column), rotational Γ rot (sixth column) and total Γ (seventh column) symmetries are also indicated.…”
Section: Ne 3 : a Lighter Systemmentioning
confidence: 99%